Komunikasi Korporasi Pada Era Industri 4.0 - Dian Amintapratiwi Purwandini; Irwansyah Irwansyah (JURNAL ILMU SOSIAL, 2018)
In the era of industry 4.0, technology is projected to dominate all aspects of human life. As a consequence, various industries must be prepared and adapt to technological developments, if they do not want to be left behind and lose. Technological development and information flow are identified as environmental factors that influence the corporation as an organization both internally and externally. This article was created using qualitative analysis methods where the literature approach is the basis for analysis. The purpose of this discussion is to find out the conceptual understanding of communication in the industrial era 4.0. The conclusion of this article is strategic and adaptive corporate communication is very important, given the exchange of information between corporations, the public and the environment will create organizational harmony so that plans and activities can be coordinated and environmental uncertainty can be reduced. The right media identification and analysis will have an impact on effective and on target corporate communication.